Optimal monetary policy and the transmission of oil-supply shocks to the euro area under rational expectations - Stéphane Adjemian; Matthieu Darracq Pariès (European Central Bank (ECB), 2008)
This paper presents first the estimation of a two-country DSGE model for the euro area and the rest-of-the-world including relevant oil-price channels. We then investigate the optimal resolution of the policy tradeoffs emanating from oil-price disturbances. Our simulations show that the inflationary forces related to the use of oil as an intermediate good seem to require specific policy actions in the optimal allocation. However, the direct effects of oil prices should be allowed to exert their mechanical influence on CPI inflation and wage dynamics through the indexation schemes. We also illustrate that any fine-tuning strategy which tries to counteract the direct effects of oil-price changes in headline inflation would prove counterproductive both in terms to stabilization of underlying inflation and by causing unnecessary volatility in the macroeconomic landscape. Finally, it appears that perfect foresight on future oil price developments allows a more rapid absorption of the steady state decline in purchasing power and real national income in the optimal allocation. Through the various expectation channels, economic agents facilitate the necessary adjustments and optimal monetary policy can still tolerate the direct effects of oil price changes on CPI inflation as well as some degree of underlying inflationary pressures in the view of easing partly the burden of downward real wage shifts. Our monetary policy prescriptions have been derived in a modeling framework where oil-price fluctuations are essentially exogenous to policy actions and where expectations are formed under the rational expectations paradigm. Notably, the extension of such conclusions to imperfect knowledge and weak central bank credibility configurations remain challenging fields for further research.
Keywords: E4; E5; F4; 330; Bayesian estimation; new open economy macroeconomics; Oil prices; optimal monetary policy; Ölpreis; Stabilisierungspolitik; Geldpolitik; Geldpolitische Transmission; Rationale Erwartung; Neue Makroökonomik offener Volkswirtschaften; Eurozone; Theorie; EU-Staaten